The Post Keynesian alternative to inflation targeting - Angel Asensio; Mark (M.G.) Hayes (Intervention. European Journal of Economics and Economic Policies, 2009)
While mainstream policies may be beyond improvement in the enchanted optimizable world, Post Keynesians have to manage without a magic wand in our uncertain world. We discuss the alternative policies proposed in the recent Post Keynesian literature and argue that control of interest rates is too imperfect for such policies to be feasible in general, although they provide useful guidelines and may be successful in favourable circumstances. Consequently, the question of credibility is irrelevant, if this means whether policy-makers will honour their commitment to an unfeasible ideal target. The right question is whether policy is convincing enough to make the conventional state of expectation (and the related interest rate) consistent with full employment. It is all a matter of confidence. The basic principles involved in such an approach to monetary policy are discussed.
Keywords: E12; E52; 330; interest rate rule; convention; uncertainty; monetary policy